Heroes, heroines, and everything in between : challenging gender and sexuality stereotypes in children's entertainment media - Olson, Christopher J.; Reinhard, CarrieLynn D. (Lexington Books, 2017)
"The past decade has seen an increase in nontraditional representations of gender and sexuality identities in children's entertainment media, keeping pace with the improved acceptance of these identities in global society and culture. This anthology collects analyses of these representations in a range of media texts from around the world"